The Horrors of Catholicism: Religion and Sexuality in Gothic Fiction - Haggerty, George (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractIn classic gothic fiction (between 1764 and 1820) a Mediterranean setting invites the expansion of Roman Catholic motifs, and indeed Catholicism itself becomes a standard and flexible trope in gothic fiction. The monastery, the convent, religious life, confessions and confessionals, nuns, monks, and friars are familiar features in gothic novels. “The Horrors of Catholicism” discusses the ways in which gothic writers use these materials to motivate their tales and what doing so means in the context of anti-Catholic eighteenth-century England. I explain how Catholic motifs can be understood in relation to other central gothic obsessions, such as sexual transgression and dysfunctional family life, and I demonstrate how these features aid novelists in exploring what would later be understood as personal sexual identity. In that way, these writers contribute to what we understand as the history of sexuality.